Buggy / Abdul Asyraf Ali Abdul Rahman ...[et al.] - Abdul Rahman, Abdul Asyraf Ali; Hamzah, Lutfi Eiman; Hamidon, Muhammad Hazim; Johari, Haziqah; Esa, Farah Nasyitah (2018)
Clingy Luggy by BUGGY is basically a futuristic innovation of luggage that carried itself without any force or effort from the owners. The concept is a worry-free luggage that comes in all-in features. It is convenient, smart and present in numbers of innovative features. This innovation helps, especially regular travellers that encounter problems with carrying their heavy bags. It also has features that helps in tracking the luggage for safety consideration. It comes with a inter-connected smart-watch which is very convenient. It is believed that this innovation can be realised as it has many advantages including penetrating the market. Medium to high class income people that usually travel are the main market target for this product. From the survey, most from the respondents agreed with the product and gives positive feedbacks.